Wereng pucuk mete Sanurus indecora J (Hemiptera: Flatidae) sebagai inang ngengat parasitoid (Epipyropidae : Lepidoptera) di pertanaman mete pulau lombok - Bambang Supeno; Pudjianto Pudjianto; Utomo Kartosuwondo (Perhimpunan Entomologi Indonesia, 2007)
This research was conducted in three areas, which has different in altitudes; those areas are Gangga (50 m), Kayangan (4 m) and Bayan (170 m) above sea levels. The aim of this research was to observe monoculture system of cashew plantations from May 2007 until April 2008. The results of this research were (1) the number of Sanurus indecora J collected from the fields are 38.619 adults, which consist of 19.153 adult of green Sanurus and 19.466 adult of white Sanurus, (2) the number of Sanurus parasitited by Epipyropidae are 5.961 adult from 38.619, (3) the number of white Sanurus infested by Epipyropidae are 3.902 adult and 2.059 adult of green Sanurus, (4) white Sanurus is preferred by Epipyropidae than green Sanurus. Around 20 percent of white Sanurus adult are infested by Epipyropidae, (5) the parsitism of female Sanurus is higher compare to male.